Socioeconomic challenges of readymade garments workers in Bangladesh: an empirical study / Dhanonjoy Kumar … [et al.] - Kumar, Dhanonjoy; Ali, Md. Jafor; Bhuiyan, Abul Bashar; Zulkifli, Norhayah (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The readymade garments (RMG) sector of Bangladesh is considered as the backbone for foreign earnings of the Bangladesh economy. Around 4.5 million of our workforces are engaged directly and about 15 million people are dependent indirectly on the apparel sector of Bangladesh. The research has identified several challenges facing the garments workers in the factory levels as well in their society, family and community. From review of the prior literature it is noted that the garment workers of Bangladesh do not have access to water and hygiene services, accommodation, first aid treatment and health services, community status, adaptation of ethnic values and customs, wage and productivity, possession arrangement affection with labor unions and leave with pay accurately. Most previous studies are within the perspective of industrialized states and targeted on the attitude of the shopping for firms solely. Recently, in Covid-19 pandemic situation Bangladesh has faced huge losses in garment sectors, many industries closed their activities, and a large number of workers lost their jobs and these problems increase day by day. The aims of this paper are to fin d out socioeconomic challenges of readymade garments employees in Bangladesh during the Covid-19 pandemic. This paper used each secondary as well as primary data. For collecting primary data111 were interviewed in Dhaka and Gazipur districts. Non-probability convenience sampling and structured questionnaires had been used and analysis conducted with Statistical Package for Social Science (SPSS). Important statistical tools and techniques i.e. factor analysis and regression analysis have been used to get authentic findings and draw a realistic conclusion. This study has implications for sustainable economic growth in Bangladesh and provides solutions to garments workers socio-economic problems. The study found that the garments workers are confronted with numerous socio-economic and psychological problems caused by Covid-19 pandemic. Now their jobs are not secured, lack of proper medical support against coronavirus, unsecured monthly wages/salary, and failure to maintain standard of living. These social imbalances have created differential attitudes towards family life and other issues crucial to the socio-economic development of our country. This study commends that for improving the ready-made garment workers socio-economic status it needs to remove the threat of loss of their job, ensure good working environment and medical facilities regarding coronavirus, ensure regular salary/ wages for maintain their standard of living for sustainable socio economic growth readymade garments workers.